Happy dreamer - Reynolds, Peter H. (Peter Hamilton), 1961- (New York : Orchard Books, an imprint of Scholastic Inc., 2017)
A "dreamer maximus" describes the many ways one can dream, and the importance of being a happy dreamer.
AD 490
Keywords: Creative ability -- Juvenile fiction; Imagination -- Juvenile fiction; Individuality -- Juvenile fiction